Informatics in Control, Automation and Robotics Selected Papers from the International Conference on Informatics in Control, Automation and Robotics 2007 - Filipe, Joaquim.; Cetto, Juan Andrade.; Ferrier, Jean-Louis. (Lecture Notes in Electrical Engineering,, 2009)
The present book includes a set of selected papers from the fourth <U+001c>International Conference on Informatics in Control Automation and Robotics (ICINCO 2007), held at the University of Angers, France, from 9 to 12 May 2007. The conference was organized in three simultaneous tracks: <U+001c>Intelligent Control Systems and Optimization , <U+001c>Robotics and Automation and <U+001c>Systems Modeling, Signal Processing and Control . The book is based on the same structure. ICINCO 2007 received 435 paper submissions, from more than 50 different countries in all continents. From these, after a blind review process, only 52 where accepted as full papers, of which 22 were selected for inclusion in this book, based on the classifications provided by the Program Committee. The selected papers reflect the interdisciplinary nature of the conference. The diversity of topics is an important feature of this conference, enabling an overall perception of several important scientific and technological trends. These high quality standards will be maintained and reinforced at ICINCO 2008, to be held in Funchal, Madeira - Portugal, and in future editions of this conference. Furthermore, ICINCO 2007 included 3 plenary keynote lectures given by Dimitar Filev (Ford Motor Company), Patrick Millot (Universit ̌de Valenciennes) and Mark W. Spong (University of Illinois at Urbana-Champaign).